Exploring Asian maternal experiences and mHealth needs for postpartum mental health care - Siti Sabrina Kamarudin; Idayu Badilla Idris; Norfazilah Ahmad; Shalisah Sharip (Digital Health)
Background Mental health care during the postpartum period is notably underexplored within Asian demographics, with barriers such as stigma, privacy concerns, logistical challenges, and a shortage of mental health professionals that limits access to optimal mental healthcare. Previous studies found that mobile health (mHealth) technology has been offering a promising solution to these issues. However, the perspectives of mothers on existing mental health services and their mHealth needs are still not well understood and warrant further exploration. Objective This study aimed to explore the postpartum experiences of Malaysian mothers with postpartum depression (PPD) symptoms and their perspectives on using an mHealth technology to improve mental health care during the postpartum period. Methods We carried out in-depth interviews with six mothers, which were transcribed verbatim and thematically analysed. Collaborative discussions and consensus were employed to enhanced reliability. Findings Five main themes related to mothers’ postpartum experiences and perspectives emerged, namely, the existing circumstances of mothers, psychosociological reactions, maternal needs, innovation of care, and suggestions for pragmatic mHealth elements. These themes emphasized the emotional challenges of meeting societal, cultural, and personal expectations. The essential resources identified to be included in the mHealth technology were education on PPD, professional guided self-care, cognitive restructuring, validation of diverse infant feeding practices, and fostering partner support. Furthermore, interactive mHealth features such as mood trackers, notifications, platforms to share, and motivational tools aimed at elevating maternal well-being were also sought. Conclusions Mothers expressed a desire for mHealth services emphasizing the need for these educational tools to be culturally sensitive, accommodating local language and religious practices, and offering support during confinement, to effectively address the unique needs of postpartum mothers. This study highlights the importance of prioritizing practical mHealth interventions as strategic support services to enhance positive postpartum mental care in resource-stricken countries.